APLIKASI TEORI GENERATIF-TRANSFORMASI DALAM PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN NURUSSALAM KRAPYAK YOGYAKARTA - Muhamad Ali Abdul Basit; Rahma Putri Kholfatul Ummah (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2018)
This research is aimed at discussing transformative generative linguistic concepts and their applications in learning Arabic. The author limits this research to the discussion of standard theory or the standard theory of generative linguistics founded by Noam Chomsky. The form of this research is qualitative while the method used is documentary by searching, collecting and analyzing written sources. The analysis was carried out descriptively to describe the object. The results of the research obtained are the application of transformative generative standard theory manifested in the form of defining language as a system internalized in individual language users so that Arabic learning is carried out based on grammar (nahwu). Learning Arabic is oriented to form broad communication competencies with grammar as the foundation. Arabic learners are directed to be individuals who are active in developing the potential of language that exists in themselves in the form of language competence (Kafa'ah al lughah) which includes grammatical, sociocultural, discourse and strategic competency.